Enhanced Antimicrobial, Cytotoxicity, Larvicidal, and Repellence Activities of Brown Algae, Cystoseira crinita-Mediated Green Synthesis of Magnesium Oxide Nanoparticles - Fouda, Amr; Eid, Ahmed M.; Abdel-Rahman, Mohamed Ali; EL-Belely, Ehab F.; Awad, Mohamed A.; Hassan, Saad El-Din; AL-Faifi, Zarraq E.; Hamza, Mohammed F. (Frontiers in Bioengineering and Biotechnology, 2022)
An eco-friendly, biocompatibility and rapid fabrication of nanoparticles by biological entities are the main advantages to overcome the limitations achieved by chemical and physical methods. Herein, magnesium oxide nanoparticles (MgO-NPs) were fabricated using brown algae, Cystoseira crinita. The fabricated MgO-NPs were characterized using UV-vis spectroscopy, Fourier transforms infrared spectroscopy, Transmission Electron Microscopy, SEM-EDX, X-ray diffraction, and X-ray photoelectron spectroscopy. The UV spectrum showed a sharp absorption peak at a maximum surface plasmon resonance of 320 nm. The obtained NPs exhibited crystalline nature and spherical NPs shapes with sizes of 3–18 nm. The Mg and O have existed in the as-formed sample with weight percentages of 54.1 and 20.6%, respectively. Phyco-fabricated MgO-NPs showed promising activities against Gram-positive bacteria, Gram-negative bacteria, and Candida albicans with MIC values ranging between 12.5 to 50 µg mL–1. Moreover, MgO-NPs were exploited clinically to target cancerous cells at lower concentrations compared with normal cell lines (IC50 was 113.4 µg mL–1 for Caco-2 cancerous cells, and 141.2 µg mL–1 for normal Vero cell line). MgO-NPs exhibited significant larvicidal and pupicidal activity against Musca domestica. An NPs at 10 µg mL–1 achieved the highest mortality at (99.0, 95.0, 92.2, and 81.0%) while the LC50 was (3.08, 3.49 and 4.46 µg mL–1), and LC90 were (7.46, 8.89 and 10.43 µg mL–1) for 1st, 2nd, 3rd instars larvae, and pupa of M. domestica, respectively. Moreover, MgO-NPs showed repellence activity for M. domestica at 10 µg mL–1 with 63.0, 77.9, 84.9, and 96.8% after 12, 24, 48, and 72h, respectively.